2016 IEEE 17th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC) 2016
DOI: 10.1109/spawc.2016.7536815
|View full text |Cite
|
Sign up to set email alerts
|

Mbps experimental acoustic through-tissue communications: MEAT-COMMS

Abstract: Methods for digital, phase-coherent acoustic communication date to at least the work of Stojanjovic, et al [20], and the added robustness afforded by improved phase tracking and compensation of Johnson, et al [21]. This work explores the use of such methods for communications through tissue for potential biomedical applications, using the tremendous bandwidth available in commercial medical ultrasound transducers. While long-range ocean acoustic experiments have been at rates of under 100kbps, typically on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…Omnidirectional transducers make the physical synchronization of a transmitter and receiver easier, whereas directional links increase the signal-to-noise ratio at the receiver, resulting in longer reachable ranges or higher data throughput support. Higher data rates can also be achieved with larger transducers, data transmission at 30 Mbps through pork meat samples is demonstrated in [28].…”
Section: B Acousticsmentioning
confidence: 99%
“…Omnidirectional transducers make the physical synchronization of a transmitter and receiver easier, whereas directional links increase the signal-to-noise ratio at the receiver, resulting in longer reachable ranges or higher data throughput support. Higher data rates can also be achieved with larger transducers, data transmission at 30 Mbps through pork meat samples is demonstrated in [28].…”
Section: B Acousticsmentioning
confidence: 99%
“…Hence, acoustic waves are considered one of the possible transmission technologies of choice for in-body communications as they are recognized to enhance the data throughput in media mostly composed of water comparing to RF signals [ 91 ]. Furthermore, Federal Communication Commission (FCC) regulations has limited the maximum allowable bandwidth that can be used for RF electromagnetic wave propagation available to Implanted Medical Devices (IMD) [ 91 ]. This therefore has greatly limited the data throughput of such devices [ 91 ].…”
Section: Candidate Wireless Technologiesmentioning
confidence: 99%
“…Furthermore, Federal Communication Commission (FCC) regulations has limited the maximum allowable bandwidth that can be used for RF electromagnetic wave propagation available to Implanted Medical Devices (IMD) [ 91 ]. This therefore has greatly limited the data throughput of such devices [ 91 ]. As an example, for frequency range of 401–406 MHz, the maximum allowable bandwidth that can be used is around 300 kHz which greatly limits the communication rates of such devices to a maximum of 50 kb/s [ 91 ].…”
Section: Candidate Wireless Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recent studies have proposed and demonstrated different protocols with varying data rates for intra-body ultrasound communication. [5][6][7][8] However, there is a large disparity in achieved rates between systems using miniaturized IMDs (~10 kbps) and prototypes using large commercial wideband transducers (~Mbps). Major unavoidable challenges arise from miniaturization including degraded bandwidth, lower directivity, and limited processing capability stemming from packaging and power constraints.…”
mentioning
confidence: 99%